Atypical thyroid manifestation in Cowden disease: a case report and literature review - Garcia, Marion; Oliver Petit, Isabelle; Franchet, Camille; Abbo, Olivier; Cartault, Audrey; Savagner, Frédérique (Frontiers in Pediatrics, 2025)
BackgroundCowden syndrome (CS) is a complex and rare hereditary disorder characterized by a high risk of developing both benign and malignant tumors. Germline variants in the PTEN gene lead to this autosomal dominant syndrome, which predisposes individuals to lesions of the skin and mucous membranes, as well as breast, thyroid, endometrial, and kidney cancers. Early identification of symptoms is essential for implementing effective therapeutic strategies, especially in managing thyroid cancer risk.Case presentationDuring a tonsillectomy in an 8-year-old boy, the surgeon incidentally noted a left lateralized thyroid swelling. The clinical picture of Cowden syndrome was further supported by the presence of macrocephaly and intellectual disability since birth along with rare and atypical thyroid disorder marked by a toxic adenoma. Genetic analysis of both the tissue and blood samples confirmed the diagnosis. The clinical manifestation of thyroid issues in a young child may indicate CS, a condition that is often poorly assessed by clinicians. Family history revealed that the boy's father and sister also carry the same heterozygous variant, presenting a spectrum of Cowden syndrome manifestations.ConclusionMolecular analysis of the PTEN gene should be considered in young patients with thyroid nodules or nodules associated with abnormal thyroid function test, even without clear evidence of Cowden syndrome, particularly if there is a family history of thyroid, breast, or hamartoma-related conditions.